Pelaksanaan Pengawasan Ketenagakerjaan Terhadap Hak Pekerja Untuk Mendapatkan Upah Kerja Lembur - Heidy Annisa Dharmawan; Agus Mulya Karsona; Holyness N. Singadimedja (Fakultas Syariah IAI Muhammadiyah Bima, 2023)
Labor inspection is a form of government policy aimed at ensuring the enforcement of labor law which is carried out by labor inspectors and equipped with certain authorities for the smooth running of labor inspection. However, in practice, it is not uncommon to find companies that are reluctant to fulfill their obligations, such as not being paid overtime wages for workers which be held for years until members of their trade unions decided to go to the field to hold public opinion demonstrations. This incident indicates a weakness in the implementation of labor inspection. This study aims to analyze the implementation of labor inspection in enforcing laws and regulations in the field of employment towards fulfilling workers rights to receive overtime wages. The research method used is normative juridical with research specifications in the form of analytical descriptive applicable laws and regulations and legal theories related to the actual practice of labor inspection. The results of the study state that the imbalance in the ratio between labor inspectors and the object of supervision causes the implementation of labor inspection to run less optimally and the fulfillment of workers rights to receive overtime pay is neglected.